Degradation of Brilliant Green by Using a bentonite Clay- Based Fe Nano Composite Film as a Heterogeneous Photo- Fenton Catalyst. (Baghdad Science Journal, 2016)
This paper aims to study the chemical degradation of Brilliant Green in water via photo-Fenton (H2O2/Fe2+/UV) and Fenton (H2O2/Fe2+) reaction. Fe- B nano particles are applied as incrustation in the inner wall surface of reactor. The data form X- Ray diffraction (XRD) analysis that Fe- B nanocomposite catalyst consist mainly of SiO2 (quartz) and Fe2O3 (hematite) crystallites. B.G dye degradation is estimated to discover the catalytic action of Fe- B synthesized surface in the presence of UVC light and hydrogen peroxide. B.G dye solution with 10 ppm primary concentration is reduced by 99.9% under the later parameter 2ml H2O2, pH= 7, temperature =25°C within 10 min. It is clear that pH of the solution affects the photo- catalytic degradation of B.G dye. All the conditions above have been studied to reach the optimum operation condition for the two processes Fenton and photo- Fenton. The B.G degradation process follows first- order reaction rules. Photo- Fenton process causes a more efficient oxidation rate than the Fenton process. So, the photo- Fenton degradation is an effective and economic process by producing higher percentage of degradation and mineralization in short radiation time.